2013
DOI: 10.1088/0953-4075/46/8/085203
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and dissociation dynamics of a water molecule under the impact of 10 keV electrons

Abstract: The kinematics and dissociation dynamics of a H2O molecule induced by 10 keV electrons are studied using a time-of-flight mass spectrometer in conjunction with a position-sensitive detector in multi-hit coincidence mode. Five dissociative channels arising from the complete as well as the incomplete Coulomb explosions of H2Oq+ (q = 2, 3) ions are observed and identified. The dissociation mechanisms (concerted and/or sequential) for these channels are examined. Further, the angular correlation of different fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
(70 reference statements)
2
8
0
Order By: Relevance
“…From the present analysis of H2O2 2+ incomplete fragmentation channel, it is found that both the slopes d s and i s are close to  -1, which is an essential condition for sequential dissociation as described in the previous work [45,46]. In addition, TOF-TOF correlation diagram 'C' (suppl.…”
Section: Enantiomeric Excesssupporting
confidence: 74%
See 2 more Smart Citations
“…From the present analysis of H2O2 2+ incomplete fragmentation channel, it is found that both the slopes d s and i s are close to  -1, which is an essential condition for sequential dissociation as described in the previous work [45,46]. In addition, TOF-TOF correlation diagram 'C' (suppl.…”
Section: Enantiomeric Excesssupporting
confidence: 74%
“…( 11) and (12). In order to understand the information regarding the sequential decay from the shapes and slopes of TOF-TOF coincidence map, selection rules set by J. H. D. Eland [45,46] have been employed. As per their rule [45], sequential decay will only be seen in the case when a neutral with low momentum fragments first leaving behind the remaining moiety with larger momentum during the first-step of incomplete-dissociation process.…”
Section: Enantiomeric Excessmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) this suprathermal distribution is associated with a large angular bond rearrangement, indicating fragmentation near the linear configuration of the water molecular ion; (iii) this suprathermal distribution has its dynamic behaviorabsolute value and energy dependence of the associated cross section identical with that for the single ionization of water and can be assigned as essentially responsible for the H 0 + O + + H 0 fragmentation channel, accounting for ∼50% of the total O + produced; (iv) the more energetic kinetic energy distributions for the O + fragment can be associated with the Auger and twosteps double ionization processes; (v) as the Auger decay and geometry rearrangement are in the 1 × 10 −15 s time scale, 41 and, at our highest measured impact energy, the collision time is within the attosecond time scale, the whole rearrangement process is clearly postcollisional and should be the same for ionization by swift heavy ions or photons as well.…”
Section: ■ Conclusionmentioning
confidence: 96%
“…The shape also introduces us to information that the detected fragment ion-pair are anti-correlated on an average with random momentum components, of the same sign and of magnitude proportional to the mass of each fragment ion [49]. From the earlier studies [49,50], the slope of the island in case of initial-charge separation process ( i s ) is given by slope, (…”
Section: Sequential Fragmentationmentioning
confidence: 99%